Crystallization and preliminary X‐ray analysis of the C‐terminal fragment of PorM, a subunit of the Porphyromonas gingivalis type IX secretion system. Issue 1 (1st January 2015) - Stathopulos, Julien; Cambillau, Christian; Cascales, Eric; Roussel, Alain; Leone, Philippe
<x xml:space="preserve">Abstract</x> PorM is a membrane protein involved in the assembly of the type IX secretion system (T9SS) from Porphyromonas gingivalis, a major bacterial pathogen responsible for periodontal disease in humans. The periplasmic domain of PorM was overexpressed in Escherichia coli and purified. A fragment of the purified protein was obtained by limited proteolysis. Crystals of this fragment belonged to the tetragonal space group P43212. Native and MAD data sets were recorded to 2.85 and 3.1 Å resolution, respectively, using synchrotron radiation.